2011
DOI: 10.3176/tr.2011.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Unity: What Students Expect From Their Teacher and Accompanist During Individual Singing Lessons

Abstract: A successful singing lesson requires coordinated efforts from the three parties involved: student, teacher, and accompanist. Results are reported of a survey in which 32 statements were rated on a 5-point Likert scale by high-school students, university students, and professional singers from an opera chorus. The statements were related to students' expectations of their teacher and accompanist during individual singing lessons. Participants were also able to add their own comments to the questionnaire. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Highlighting that clear, effective, and positive communication is one of the empathic behaviors of voice teachers (Lewis & Hendricks, 2022), this study resonates with Stojiljković et al’s (2014) finding that training through social activities can contribute to developing an empathic practice. As students appear to seek trustworthy relationships with their teachers (Kiik-Salupere & Ross, 2011; Lewis & Hendricks, 2022), voice teachers should be trained to actively seek to understand their students through responsive listening (Parker, 2007). Above all, developing empathetic pedagogies must consider that voice teachers use multiple, intertwined empathic characteristics in their practices, and that the development of these can benefit not only their teaching but also their (future) students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Highlighting that clear, effective, and positive communication is one of the empathic behaviors of voice teachers (Lewis & Hendricks, 2022), this study resonates with Stojiljković et al’s (2014) finding that training through social activities can contribute to developing an empathic practice. As students appear to seek trustworthy relationships with their teachers (Kiik-Salupere & Ross, 2011; Lewis & Hendricks, 2022), voice teachers should be trained to actively seek to understand their students through responsive listening (Parker, 2007). Above all, developing empathetic pedagogies must consider that voice teachers use multiple, intertwined empathic characteristics in their practices, and that the development of these can benefit not only their teaching but also their (future) students.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified that teacher empathy enables successful communication (Berkovich, 2020; Goroshit & Hen, 2016; Stojiljković et al, 2012) and connection with students (Arghode et al, 2013; Hutton, 2022). For voice teachers, empathy is essential for training students both physically and psychologically (Kiik-Salupere & Ross, 2011). A voice teacher’s success with their students is reportedly linked to their ability to empathize and demonstrate care (Helding, 2017b; Hendricks, 2022); support their student’s ability to cope in the performing arts industry (Kiik-Salupere & Ross, 2011); generate trust through demonstrating knowledge, experience, and candor (Lewis & Hendricks, 2022); and assist in diagnosing vocal issues in students (Brown, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing amount of research has begun to investigate the nature of interactions in studio lessons without necessarily distinguishing between singers and instrumentalists, and this work has employed a wide range of methodological approaches to highlight different aspects of the subject. For example, the perceptions and attitudes of lesson participants have been sought through a survey of high-school pupils, university students and professional singers (KIIK-SALUPERE;ROSS, 2011), and mixed groups of singers and instrumentalists have participated in interviews and focus groups, encouraged to engage in "storytelling and reflection" (CAREY; GRANT, 2015, p. 7). In other studies, interviews have been used in conjunction with video observation, to collect richer data about studio participants' own understanding of their practices (BURWELL, 2012;BURWELL, 2016a;JAMES et al, 2010;JOHANSSON, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%